Evaluating different values of effort and reinforcement parameters under concurrent‐ and single‐operant arrangements. Issue 2 (12th December 2018) - Lozy, Erica D.; Sy, Jolene R.
Abstract : If particular parameters (e.g., reinforcer quality) are found to be preferred in a concurrent‐operant arrangement, then these should be incorporated into interventions for maintaining skills in individuals with intellectual disabilities. However, because results from a concurrent‐operant arrangement may not predict those of a single‐operant assessment, interventions with less preferred parameters may also be effective. The purpose of this study was to determine if preference for a particular parameter, determined via concurrent‐operant arrangements, predicted responding when two values of highly and less preferred parameters were manipulated in a single‐operant arrangement. Participants allocated responding to one parameter over another during concurrent‐operant assessments, indicating that certain parameters were highly preferred. However, contingent presentation of two values of less preferred parameters increased compliance to similar levels achieved with two highly preferred parameters in a single‐operant arrangement. These findings suggest that clinicians may have multiple options when selecting parameters for use during intervention.